Dynamics of Hydration of Nanocellulose Films. Issue 5 (28th December 2015) - Bettotti, Paolo; Maestri, Cecilia Ada; Guider, Romain; Mancini, Ines; Nativ‐Roth, Einat; Golan, Yuval; Scarpa, Marina
Abstract : The design of materials capable of mechanical responses to physical and chemical stimuli represents one of the most exciting and challenging areas of scientific research because of the huge number of their potential applications. This article is focused on the molecular events occurring in thin films of carboxylated nanocellulose fibers, which are capable of converting water gradients into mechanical movements at the macroscopic scale. The analysis of the mechano‐actuation, and of the conditions to obtain it, shows that the film movement is fast and reproducible, the gradient intensity is transduced into rate of displacement, and the response is observed at vapor pressures as low as 1.2 mm Hg. The actuation mechanism is associated to an efficient and reversible water sorption process by the hydrophilic nanocellulose fibers at the film interface. Conversely, water desorption is slow and follows a kinetic behavior supporting the presence of two binding sites for water molecules. The adsorbed water induces swelling of the surface nanocellulose layers and local structural rearrangement, however transitions between ordered and random coil conformations are not observed. The understanding of the actuation mechanisms of nanocellulose offers exciting opportunities to design macroscopic structures responding to chemical gradients by the assembly of simple molecular components. Abstract : Films of carboxylated nanocellulose convert gradient‐driven water fluxes into mechanical movements. Multiple experimental techniques are used to investigate the film dynamics at the molecular level and find the relationship with the macroscopic response of the film. The understanding of this interfacial process provides the ground for the design of actuators responding to chemical gradients.